The role of English in intercultural communication: Past, modernity and future global perspectives - Leona L. Grigoryeva; Roza R. Zakirova (Peoples' Friendship University of Russia (RUDN University), 2022)
The problem of interconnection between language and intercultural relations has been widely discussed by researchers worldwide. This article studies the relationships between culture and language, examining the reasons for English dominance in the world, defining the current status of its global spread, and highlighting its future perspectives as a global language in intercultural communication. The research is based on the analysis and generalisation of contemporary studies on the related topics and compares the most recent statistical data. Study results suggest that although English is not in first place, judged by the number of native speakers in the world, it is by far the most learnt foreign language in the world due to both linguistic and extralinguistic factors. As far as future global perspectives are concerned, English is likely to remain a global language in the near future, but it will probably acquire new forms and experience many changes in its syntactic, grammatical, and semantic structures. The study concludes that the use of English helps users achieve better intercultural understanding, making intercultural relations clear, productive, and timesaving. The study contributes to the development of the essence of the concept of an international language in its relation to culture, the formulation of factors for a particular language to acquire global status, the development of the notion of a lingua franca, and the promotion of intercultural understanding.